ESTABLISHMENT OF HONESTY PRINCIPLES APPLICATION POLICY IN FIRE INSURANCE AGREEMENTS IN INDONESIA - Ronni Prima Dinata (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
A form of insurance that guarantees loss and damage due to fire or the risk of its expansion affecting the object of coverage Objects that can be insured are in the form of your property in the form of residential buildings, shop houses, warehouses, factories, office buildings, hotels, household furniture, home appliances, machinery , merchandise, inventory of raw materials or finished goods, and so on in accordance with the Indonesian Fire Insurance Standard Policy (PSAKI). This insurance is also known as All Property Risk Insurance. In the law or insurance agreement there is the principle of honesty. the principle of honesty is the principle for every insurance agreement that is in the provisions of the Civil Code. Article 251 of the Commercial Code also regulates good faith or honesty, this is because insurance agreements have special characteristics, compared to other agreements in the Civil Code. The Insured must be aware that it has an obligation to provide true, honest and complete information regarding the condition of the insured object. Article 251 emphasizes that the principle of good faith or honesty is only for the insured. Insurance is one type of special agreement regulated in the Commercial Code as an agreement, so the provisions of the legal terms of an agreement in the Civil Code also apply to insurance agreements. The legal terms of an agreement are regulated in Article 1320 of the Civil Code, there are 4 valid conditions for an agreement, namely the agreement of the parties, the authority to act, certain objects, and lawful causes.